Prospective investigation of serial ultrasound for transient tachypnea of the newborn - Chung-Sing Li; Shih-Ming Chu; Reyin Lien; Tze-Yee Mok; Kai-Hsiang Hsu; Shen-Hao Lai (Elsevier, 2021)
Background: Transient tachypnea of the newborn (TTN), which is diagnosed using typical clinical course and radiographic findings, is the most common cause of respiratory distress in late-preterm and term neonates. Lung ultrasound (LUS) is increasingly used to identify TTN according to the distinct characteristics of the disease. However, few studies have reported the application of LUS to monitor the clinical evolution of TTN. Using serial LUS, this prospective study assessed and monitored TTN severity. Methods: From November 2018 to October 2019, neonates ≥34 weeks of gestation admitted to the newborn center of Chang Gung Memorial Hospital were enrolled. Neonates diagnosed with TTN and requiring respiratory support comprised the TTN group (n = 29), whereas those without respiratory disease served as the control group (n = 23). LUS was performed and scored in both groups within 4 h of admission and followed up at 24 and 48 h. Results: A total of 65 infants were screened for enrollment and 13 were excluded. Most of the enrollees in both groups exhibited a peak LUS score on the first day, which then gradually declined thereafter. In comparison with the control group, the LUS score of the TTN group was higher on day 1 and day 2, and it had a significantly greater decrease from day 1 to day 2. In the TTN group, LUS scores moderately correlated with respiratory severity scores. Conclusion: We conducted a serial and quantitative LUS investigation in late-preterm and term infants with TTN. The LUS score mirrored the respiratory status relatively well, and it can help to monitor the clinical course of TTN, in the case of either resolution or deterioration.